Wilson disease in the USA: epidemiology and real-world patient characteristics based on a retrospective observational health claims study - Karl Heinz Weiss; Peter Hedera; Shona Fang; Carey Strader; Halley Costantino (BMJ Open)
Objectives To describe the epidemiology, patient characteristics and comorbidities in patients with Wilson disease (WD) in the USA.Design Retrospective, population-based study.Setting The study used the US Komodo claims database containing records regarding medical claims for over 120 million individuals.Participants Patients with WD were identified via ICD-10 (10th revision of the International Classification of Diseases) code during the study period 2016–2019 and no age restriction was applied. A further stratification by disease subtype (‘hepatic’, ‘neurologic’ and ‘psychiatric’) was performed.Main outcome measures WD prevalence was reported by age, sex and US census regions/divisions. Adjusted prevalence was calculated using age-specific prevalence standardised to the USA (2010 US census) and to the world (WHO 2000–2025) to enable comparisons across countries, using direct standardisation of prevalence estimates by age group.Results Overall, 2115 patients with WD were identified during the study period. Among them, 56.8% had hepatic symptoms, 57.0% neurologic symptoms and 47.4% psychiatric symptoms. The most frequent manifestations in hepatic patients were liver signs and symptoms (90.8%), in neurologic patients cognitive defects (50.7%) and in psychiatric patients mood disorders (86.4%). The mean age in the overall cohort was 39.9 years. Prevalence estimation was based on 1481 patients with WD between 2017 and 2019. The 2017–2019 crude period prevalence was 21.2 patients per million (95% CI: 20.1 to 22.3), with similar prevalence observed for both sexes.Conclusions This study provides important real-world data on the diagnosed prevalence of WD in the USA and revealed the comorbidities associated with various disease subtypes, thereby providing a comprehensive basis for guiding physicians and policy makers in the management of this chronic disease.